The impact of the "RunSmart" running programme on participant motivation, attendance and well-being using self-determination theory as a theoretical framework. Issue 1 (2nd January 2022) - Johnson, Laura J.; Cronin, L.; Huntley, E.; Marchant, D.
ABSTRACT: Running is a popular and convenient form of leisure-time physical activity, with participation levels increasing in the United Kingdom in low physical activity groups such as women and overweight individuals, following the introduction of schemes such as Couch to 5km (C25 K). However, despite the popularity of these programmes, there is little research into the social and psychological processes involved in effective engagement and long-term behaviour changes. Therefore, the aim of the study was to explore the impact of participation in a 10-week group-led beginners running programme on participant motivation, attendance and well-being using Self-Determination Theory (STD) as a theoretical framework. Participants ( N = 124; Mage = 40.74) were recruited from a beginners' running programme based in the North West of England and self-completed questionnaires during weeks 2, 6 and 10. Future intentions to run were also assessed at 3- and 6-month follow up. Results demonstrated the positive impact an adapted C25 K model can have upon elements of self-perceptions (particularly perceived competence) and future intentions to run. The path analysis, which looked at average values over time, demonstrated that leader autonomy support positively impacted upon participants' basic needs satisfaction, which led to the development of more self-determined motivation, and in turn led to higher levels of attendance and mental well-being. Critically for drop-out, results from multiple regression analysis indicated that individuals with a higher BMI rated leader autonomy support as lower and felt less competent during the programme. A number of research and practical recommendations are discussed.